Pengembangan Media Pembelajaran Matematika Berbasis CTL Berbantuan Macromedia Flash untuk Meningkatkan Kemampuan Visual Thinking Siswa SMP - Deliana, Deliana; Surya, Edi; Fauzi, Kms Muhammad Amin (Mathematics Education Study Program, 2023)
Visual thinking skills play a role in solving problems from questions that require high-level reasoning. Based on the facts in the field, it can be seen that students' visual thinking abilities are still low, students are still unable to visualize the components contained in a flat-sided shape. This research has several objectives: (1) To determine the validity, practicality, and effectiveness of developing learning media assisted by Macromedia Flash using CTL-based learning; and (2) to find out the increase in visual thinking skills of junior high school students through CTL-based mathematics learning media assisted by Macromedia Flash. This research includes development research. This study uses the 4-D Thiagarajan development model. The subjects in this study were students of class VIII-A at Al-Manar Private Middle School, Medan, Johor. Meanwhile, the object of this study is the learning media assisted by Macromedia Flash, the materials developed for Flat Sided Spaces (Cubes and Blocks). The results of this study indicate that: (1) The developed mathematics learning media also meets valid, practical, and effective criteria; (2) Improving students' visual thinking abilities using learning media developed on cube and block material, the average value increased from trial I of 67.91 to 74.16 in trial II. The developed Macromedia Flash-assisted learning media has fulfilled the aspects of validity, practicality, effectiveness, so it is recommended for teachers to be able to use this learning media to develop visual thinking skills, especially for class VIII of Al-Manar Private Middle School Medan.